Care arrangements, disability and family contingencies in Solomon Islands: a comparative example. (3rd May 2016) - Manderson, Lenore; Gartrell, Alexandra; Jennaway, Megan; Fangalasu'u, Judith; Dolaiano, Simon
Abstract : In official and normative discourses on disability and social inclusion in the Pacific and globally, family structure and composition is often represented as stable and culturally consistent. Following from this, policy statements and programmes are routinely based on the expectation that family members will be involved in the care and support of people with disability. Drawing on ethnographic data from Solomon Islands, we highlight the variability of contemporary domestic arrangements of people with disability. Family structure and the social relationships that constitute them in Solomon Islands are complex and changing, based upon a dynamic mix of cultural, historical and economic factors. While nuclear, joint and extended family structures all occur, within both matrilineal and patrilineal systems, only one or two people are able and willing to provide everyday assistance to family members who need personal and other care. Economic activity, perceptions of time and availability, and social exigencies all shape which people provide care and the quality of care they extend.